Expanding expected goals methodology in field hockey - Myers, B. R.; Daly, A. M. (The Sport Journal, 2023)
The purpose of this study is to demonstrate the value of the overarching expected goals methodology in the sport of field hockey by examining performance data in NCAA Division I Field Hockey. Expected Goals (xG), a metric used to represent the likelihood of a shot being a goal, has grown in popularity across multiple sports. The expected goals methodology involves model building through logistic regression. Specifically, two metrics are created through this technique: 1) The standard expected goals model (xG) based on characteristics of the scoring opportunity before the shot is taken and 2) Post-shot expected goals (xGOT) which is updated to reflect whether or not the shot is on target.